Metabolomic Analysis of Hexagenid Mayflies Exposed to Sublethal Concentrations of Naphthenic Acid - Pomfret, Sarah M.; Brua, Robert B.; Milani, Danielle; Yates, Adam G. (Frontiers in Molecular Biosciences, 2021)
The oil sands region in northeastern Alberta, Canada contain approximately 165 billion barrels of oil making it the third largest oil reserves in the world. However, processing of extracted bitumen generates vast amounts of toxic byproduct known as oil sands process waters. Naphthenic acids and associated sodium naphthenate salts are considered the primary toxic component of oil sands process waters. Although a significant body of work has been conducted on naphthenic acid toxicity at levels comparable to what is observed in current oil sands process waters, it is also important to understand any impacts of exposure to sublethal concentrations. We conducted a microcosm study using the mayfly Hexagenia spp. to identify sublethal impacts of naphthenic acid exposure on the survival, growth, and metabolome across a concentration gradient (0 - 100 µg L-1) of sodium naphthenate. Nuclear magnetic resonance-based metabolomic analyses were completed on both the polar and lipophilic extracted fractions of whole organism tissue. We observed a positive relationship between sodium naphthenate concentration and mean principal component score of the first axis of the polar metabolome indicating a shift in the metabolome with increasing naphthenic acid exposure. Eleven metabolites correlated with increased naphthenic acid concentration and included those involved in energy metabolism and apoptosis regulation. Survival and growth were both high and did not differ among concentrations, with the exception of a slight increase in mortality observed at the highest concentration. Although lethal concentrations of naphthenic acids in other studies are higher (150 - 56200 µg L-1), our findings suggest that physiological changes in aquatic invertebrates may begin at substantially lower concentrations. These results have important implications for the release of naphthenic acids into surface waters in the Alberta oil sands region as an addition of even small volumes of oil sands process waters could initiate chronic effects in aquatic organisms. Results of this research will assist in the determination of appropriate discharge thresholds should oil sands process waters be considered for environmental release.